2007
DOI: 10.1002/met.20
|View full text |Cite
|
Sign up to set email alerts
|

The representativeness problem of a station net applied to the verification of a precipitation forecast based on areas

Abstract: ABSTRACT:The results and conclusions obtained in a verification process can be strongly influenced by its methodology, especially when some assumptions are made in order to avoid the limitations of the observational data (i.e., the lack of representativeness of the data or poor area coverage). Several aspects of the verification process must be studied if reliable conclusions are to be obtained. This paper discusses the problems related to the development of a verification method for a precipitation forecast d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…10a) that the combined product includes the small-scale variability of radar data. Our results confirm with the findings of Moszkowicz (2000), Bárdossy and Brommundt (2008) and Datta et al (2003), where radar data are considered as a practical instrument to preserve the information of the small scale variability of precipitation. The studies showed high correlation values of radar data for low distances.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…10a) that the combined product includes the small-scale variability of radar data. Our results confirm with the findings of Moszkowicz (2000), Bárdossy and Brommundt (2008) and Datta et al (2003), where radar data are considered as a practical instrument to preserve the information of the small scale variability of precipitation. The studies showed high correlation values of radar data for low distances.…”
Section: Discussionsupporting
confidence: 91%
“…Here, the comparison between the BIAS values of a one hour time step to the average BIAS of short-time periods (8 hours) showed a decreasing value with increasing time scale. Ballester and Moré (2007) reported similar results for precipitation events between 0.2 and 0.4 mm for time scales between 12 and 36 h. Our study confirmed with the known tendency of radar to underestimate gauge measurements for small rain rates. The HSS for convective rain was not as high as for advective events.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Further, these results support the choice of the simulation domain as well achieved in simulating the month precipitation where one has to pay attention to problems with discontinuities due to orographic complexities. Citing Ballester and Moré (2007), "On the other hand, if the areas are large enough, weather forecast uncertainties derived from spatial precipitation discontinuities can more easily be avoided, especially in areas with complex orography and a high frequency of convection phenomena".…”
Section: Discussionmentioning
confidence: 99%